Pengaruh Kontrol Diri dan Kecemasan Terhadap Prokrastinasi Pecinta Alam Uin Syarif Hidayatullah Jakarta - Mustikaningsih, Rahajeng; Saloom, Gazi; Tresniasari, Nia (TAZKIYA Journal of Psychology, 2013)
This reasearch was done in order to know influence of self control toward anxiety of academicprocrastination among students joining in organizations of natural lovers. It used quantitativemethod by distributing scales of self control and anxiety of academic procrastination tostudents who have been chosen as samples. The result of reaserch showed that self control hasbig impact toward anxiety of academic procrastination among students. This researchsupported previous reasearches about anxiety of academic procrastination. Suggestions relatedto the result‟s research was discussed.